Neutrophil Count and Level of Interleukin-1β and Interleukin-8 in the Saliva of Three to Five Year Olds with and without Dental Caries - Maryam Seyedmajidi; Effat Khodadadi; Ghorban Maliji; Mohammadali Zaghian; Ali Bijani (Tehran University of Medical Sciences, 2016)
Objectives: Saliva plays an important role in prevention of dental caries. Neutrophils are the first defense mechanism of the immune system. Interleukins (ILs) can regulate the activity of neutrophils. This study aimed to assess the neutrophil count and level of IL-lβ and IL-8 in the saliva of children with and without dental caries. Materials and Methods: This case-control study was performed on 90 preschool children between three to five years. Children were divided into three groups of caries-free, early childhood caries (ECC) and severe early childhood caries (S-ECC). Saliva was collected in tubes by the spitting method. Neutrophil count was assessed by Giemsa staining and the levels of IL-lβ and IL-8 in the saliva were assessed using ELISA. Data were analyzed by the Kruskal-Wallis and post hoc Games-Howell test. Results: The mean levels of IL-1β and IL-8 and the mean neutrophil count in the caries free group were found to be 59.2± 59.15 pg/mL, 86.04± 96.12 pg/mL and 1342.66± 2222.412 pg/mL, respectively. These values were 36.78± 40.88 pg/mL, 76.12± 107.01 pg/mL and 2500± 3834.61 pg/mL in the ECC group and 48.75±47 pg/mL, 76.77± 70.63 pg/mL and 2353.1± 4583.81 pg/mL in the S-ECC group, respectively. There were no significant differences among the three groups in terms of the levels of IL-1β, IL-8 or the neutrophil count (P>0.05). Conclusion: Since no significant difference was noted in the salivary levels of IL-1β and IL-8 or the neutrophil count among the groups, development of dental caries may be related to neutrophil chemotaxis defect.